The case of Darwinylus marcosi (Insecta: Coleoptera: Oedemeridae): A Cretaceous shift from a gymnosperm to an angiosperm pollinator mutualism - Peris, David (Commun Integr Biol, 2017)
Abundant gymnosperm pollen grains associated with the oedemerid beetle Darwinylus marcosi Peris, 2016 were found in Early Cretaceous amber from Spain. This discovery provides confirmatory evidence for a pollination mutualism during the mid Mesozoic for the family Oedemeridae (Coleoptera), which today is known to pollinate only angiosperms. As a result, this new record documents a lateral host-plant transfer from an earlier gymnosperm to a later angiosperm, indicating that pollination of the latter is a derived condition within Oedemeridae. This new fossil record exemplifies one of the 4 ecological-evolutionary pollinator cohorts now known to have existed during the global shift from a gymnosperm to an angiosperm dominated global flora. Currently, all direct evidence for pollination during the 35 million-year interval of the mid Cretaceous gymnosperm-to-angiosperm transition entails recognition of gymnosperm pollen grains on insect mouthparts and other body contact surfaces, while analogous records involving angiosperms are lacking. The gathering evidence indicates that angiosperm pollination was preceded by at least 4 gymnosperm pollination modes that served as a functional and ecological prelude to the rise and expansion of angiosperms.